2021
DOI: 10.1016/j.tacc.2020.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of awake prone positioning in COVID-19 patients- A systematic review

Abstract: Background Prone positioning is known to reduce mortality in intubated non-COVID-19 patients suffering from moderate to severe acute respiratory distress syndrome (ARDS). However, studies highlighting the effect of awake proning in COVID-19 patients are lacking. We aim to conduct a systematic review of the available literature to highlight the effect of awake proning on the need for intubation, improvement in oxygenation and mortality rates in COVID-19 patients with ARDS. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
0
21
0
2
Order By: Relevance
“…A recent systematic review found no existing data that describe the effect of serial prone positioning on oxygenation beyond the initial episode. 18 Two previous studies applied multiple episodes of APP, but do not present longitudinal data. 19 20 Importantly, the median duration of APP in our study was around 2 hours; comparable with early clinical trials investigating APP in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found no existing data that describe the effect of serial prone positioning on oxygenation beyond the initial episode. 18 Two previous studies applied multiple episodes of APP, but do not present longitudinal data. 19 20 Importantly, the median duration of APP in our study was around 2 hours; comparable with early clinical trials investigating APP in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In the 2017 meta-analysis of data from >2100 proned, mechanically ventilated patients with ARDS, outcomes data were not sex-disaggregated, and published data on proned patients with COVID-19 are thus far limited. 71,73,75 Although there are S/G differences in the need for ICU admission, once in a unit there are no S/G differences in mortality, as shown by a recent global meta-analysis involving data from >16,000 patients with COVID-19. 76 A total of 69% of ICU-admitted patients were male, there were no S/G differences in ICU mortality,~68% of patients overall required intubation, and 28% died.…”
Section: Biological Sex and Pulmonary Manifestations Of Covid-19mentioning
confidence: 99%
“…70 During the initial stages of the pandemic, it was common practice to intubate mildly hypoxic patients, even if they clinically appeared otherwise well; however, as this practice did not appear to benefit many patients, strategies to help avert early intubation have become increasingly popular. 71 Previous research on ARDS has shown that proning intubated patients can significantly decrease mortality. 72,73 A meta-analysis of data on proning spontaneous-breathing patients with COVID-19 suggested an improvement in oxygenation and likely a decreased need for subsequent intubation.…”
Section: Biological Sex and Pulmonary Manifestations Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Health care workers (HCWs) are in the front line of COVID-19 patients’ management, thus, they are facing constantly higher risk of infection than the wider community [ 3 ]. On the other hand, COVID-19 has affected quality of life, psychological condition, and training of HCWs, as shown in recent studies [ 4 , 5 , 6 , 7 ]. Several recommendations have been published from national and international societies, such as the World Health Organization (WHO) regarding the prevention and control of COVID-19 for HCWs [ 8 ].…”
Section: Introductionmentioning
confidence: 99%